2011
DOI: 10.4093/dmj.2011.35.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Inhibits Insulin Binding to Endothelial Cells

Abstract: BackgroundInsulin-mediated glucose uptake in insulin target tissues is correlated with interstitial insulin concentration, rather than plasma insulin concentration. Therefore, insulin delivery to the interstitium of target tissues is very important, and the endothelium may also play an important role in the development of insulin resistance.MethodsAfter treating bovine aortic endothelial cells with angiotensin II (ATII), we observed the changes in insulin binding capacity and the amounts of insulin receptor (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
4
1
1
Order By: Relevance
“…Ang II increases blood flow, but appears to impair insulin-mediated glucose metabolism, without altering the access of insulin to the muscle interstitium [89]. These data on insulin access are not consistent with other published data, indicating that Ang II can reduce the number of insulin receptors on endothelial cells, which may lead to a reduction in receptor-mediated transcytosis [90], if insulin transport is indeed receptor-mediated. Some of these inconsistences may be due to the time of exposure to the vasoconstrictor: one study has shown that short-term Ang II can increase NO production, but long-term can reduce NO bioavailability [91].…”
Section: Factors That Can Induce Capillary Recruitmentcontrasting
confidence: 64%
“…Ang II increases blood flow, but appears to impair insulin-mediated glucose metabolism, without altering the access of insulin to the muscle interstitium [89]. These data on insulin access are not consistent with other published data, indicating that Ang II can reduce the number of insulin receptors on endothelial cells, which may lead to a reduction in receptor-mediated transcytosis [90], if insulin transport is indeed receptor-mediated. Some of these inconsistences may be due to the time of exposure to the vasoconstrictor: one study has shown that short-term Ang II can increase NO production, but long-term can reduce NO bioavailability [91].…”
Section: Factors That Can Induce Capillary Recruitmentcontrasting
confidence: 64%
“…Each of these actions of Ang II can independently impair the vasodilatory actions of insulin in the microvasculature. In addition to these deleterious actions, Ang II directly impairs insulin signaling pathways in the endothelium (Kim, Jang, Martinez-Lemus et al, 2012, Maeno, Li, Park et al, 2012, Andreozzi, Laratta, Sciacqua et al, 2004, Oh, Ha, Lee et al, 2011, Presta, Tassone, Andreozzi et al, 2011). …”
Section: Angiotensin II and Pathway-selective Insulin Resistance Imentioning
confidence: 99%
“…Ang II impairs the activity and interaction of these critical nodes in the endothelium. Treatment of bovine aortic endothelial cells with Ang II decreases the number of insulin receptors (IR) in the membrane (Oh et al, 2011). Although, the intracellular mechanisms mediating the reduction in IR are yet to be elucidated, this effect was reversed by ATR blocker.…”
Section: Angiotensin II and Pathway-selective Insulin Resistance Imentioning
confidence: 99%
“…For example, Ang II can decrease the number of insulin receptors in the membrane in bovine aortic endothelial cells. 33 Ang II leads to phosphorylation of insulin receptor substrates at Ser 636/639 through activating mTOR/p70S6K and inhibits the insulin-stimulated phosphorylation of eNOS via AT 1 R. 34 Insulin-induced capillary recruitment is abrogated, and glucose disposal is attenuated after the treatment with AT 2 R antagonist, PD123319. 35 However, correlation between AT 2 R and insulin receptor on sodium transport in kidney remains undetermined.…”
Section: Discussionmentioning
confidence: 99%